Implementasi Laudato Si’ sebagai Upaya Membangun Kesadaran Ekologis - Age, Maria Yulita C; Atasoge, Anselmus D; Dhedhu, Frederikus (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The study, which is the implementation of community service organized by STIPAR Ende, wants to focus on how the praxis of community life around the Wolowona river coast, the response of the community around the Wolowona river coast to the existence of the Wolowona river and pastoral efforts to sustain the existence of the Wolowona river. From the star point, this study aims to explore the understanding and praxis of ecological life of the community towards the existence of the Wolowona river from a pastoral perspective in the light of the encyclical Laudato Si' written by Pope Francis. This community service activity was carried out using the drump up method, namely the act of raising awareness from lack of understanding to understanding. The steps taken are: First, conducting social reflection/discussion/FGD with residents who live around the Wolowona riverbank. Second, the emergence of ecological awareness, namely the awareness to maintain and care for the Wolowona river. Third, building an agreement with residents to work together or collaborate to clean Wolowona river and prepare public trash bins in the Wolowona riverbank area. The ecological awareness of residents in the area around the Wolowona riverbank is still quite low. Therefore, it is necessary to build awareness in residents about the importance of maintaining and preserving the Wolowona river as part of the overall ecological system. Residents need to be assisted to strengthen their understanding of the relationship between humans and the universe with the ultimate goal of maintaining, caring for and preserving the existence of the Wolowona river. Pope Francis emphasized the need for active participation from all levels of society in protecting the environment. To achieve this, the following are some practical suggestions. First, the government of Ende Regency with the Environmental Agency as the leading sector, together with the residents, must be able to ensure that the water from this river remains clean. Second, people should not use the river as a place to throw garbage. Third, to reduce the amount of waste such as plastic waste, it is hoped that residents can avoid using disposable plastics. Fourth, it is expected that residents have the awareness to keep the trash bins and utilize them according to their designation. Fifth, the Church as a moral institution continues to advocate its members to maintain and care for ecology as part of their expression of faith.